2017
DOI: 10.1186/s13033-017-0135-5
|View full text |Cite
|
Sign up to set email alerts
|

An overview of mental health care system in Kilifi, Kenya: results from an initial assessment using the World Health Organization’s Assessment Instrument for Mental Health Systems

Abstract: BackgroundLittle is known about the state of mental health systems in Kenya. In 2010, Kenya promulgated a new constitution, which devolved national government and the national health system to 47 counties including Kilifi County. There is need to provide evidence from mental health systems research to identify priority areas in Kilifi’s mental health system for informing county health sector decision making. We conducted an initial assessment of state of mental health systems in Kilifi County and documented re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
3
32
0
Order By: Relevance
“…The extent of the cognitive problems in epilepsy in this study is even substantially greater than can be inferred from results from these cognitive tests, considering that 37% of the adults with epilepsy were unable to complete the executive function tests, and likely represents severe disability in PWE, who perhaps require special support and care including rehabilitation. Unfortunately, a recent situation analysis showed that such services are not available for people living with mental health problems in this area [39] . Although care for children with disabilities including rehabilitation services has been given some attention in this area [40] , the focus should also be extended to the adults and the aging populations in whom disabilities are also common.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of the cognitive problems in epilepsy in this study is even substantially greater than can be inferred from results from these cognitive tests, considering that 37% of the adults with epilepsy were unable to complete the executive function tests, and likely represents severe disability in PWE, who perhaps require special support and care including rehabilitation. Unfortunately, a recent situation analysis showed that such services are not available for people living with mental health problems in this area [39] . Although care for children with disabilities including rehabilitation services has been given some attention in this area [40] , the focus should also be extended to the adults and the aging populations in whom disabilities are also common.…”
Section: Discussionmentioning
confidence: 99%
“…The literacy levels are low and this area is one of the poorest administrative regions in Kenya. The health care system for mental and neurodevelopmental disorders in this area is poorly developed ( Bitta, Kariuki, Chengo, & Newton, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Within Kilifi County Hospital, there is one specialist psychiatric clinic, which is run by a specialized psychiatric nurse and serves up to 70 patients a day. The common problems presented are schizophrenia/psychosis, seizure disorders followed by depression and other mood disorders ( Bitta et al , 2017 ). There were no formal measures of evaluation and diagnosis of depression at the time of this study.…”
Section: Methodsmentioning
confidence: 99%